(untitled) (Nuntius Antiquus, 2012)
Abstract: This study proposes an interpretation of Pindar’s Olympian 12 with particular attention to the theme of contingency (according to Aristotle, “that which may be otherwise”) in relation to human action. As the course of the athlete’s life and of the political history of Himera, the poem and its water images move through uncertainties and reach the accomplishment. Although Pindar recognizes the risks of hope, he shows how the constant variations of human life and the impossibility of knowing the future can result in a positive reversion of conditions in which an adverse situation leads to achievement, even when it is unlikely.